Contextual Factors Explain Risk-Seeking Preferences in Rhesus Monkeys - Heilbronner, Sarah; Hayden, Benjamin (Frontiers in Neuroscience, 2013)
In contrast to humans and most other animals, rhesus macaques strongly prefer risky rewards to safe ones with similar expected value. Why macaques prefer risk while other animals typically avoid it remains puzzling and challenges the idea that monkeys provide a model for human economic behavior. Here we argue that monkeys’ risk-seeking preferences are neither mysterious nor unique. Risk-seeking in macaques is possibly induced by specific elements of the tasks that have been used to measure their risk preferences. The most important of these elements are (1) very small stakes, (2) serially repeated gambles with short delays between trials, and (3) task parameters that are learned through experience, not described verbally. Together, we hypothesize that these features will readily induce risk-seeking in monkeys, humans, and rats. Thus, elements of task design that are often ignored when comparing studies of risk attitudes can easily overwhelm basal risk preferences. More broadly, these results highlight the fundamental importance of understanding the psychological basis of economic decisions in interpreting preference data and corresponding neural measures.